2022
DOI: 10.1037/pha0000462
|View full text |Cite
|
Sign up to set email alerts
|

Use patterns, beliefs, experiences, and behavioral economic demand of indica and sativa cannabis: A cross-sectional survey of cannabis users.

Abstract: Cannabis products available for retail purchase are often marketed based on purported plant species (e.g., "indica" or "sativa"). The cannabis industry frequently claims that indica versus sativa cannabis elicits unique effects and/or is useful for different therapeutic indications. Few studies have evaluated use patterns, beliefs, subjective experiences, and situations in which individuals use indica versus sativa. A convenience sample of cannabis users (n = 179) was surveyed via Amazon Mechanical Turk (mTurk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Among consumers, the terms sativa , indica , and hybrid are used colloquially and are associated with perceived effects [ 37 ]. Sativa has been associated with stimulating effects, indica with sedating effects, and hybrids are perceived to be bred from the former two to fit the more personalized needs of consumers [ 23 , 24 , 35 , 37 ]. Interestingly, a recent study collected data characterizing various commercial products classified as sativa , indica , or hybrid and used supervised and unsupervised machine learning algorithms to subjective effect tags [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among consumers, the terms sativa , indica , and hybrid are used colloquially and are associated with perceived effects [ 37 ]. Sativa has been associated with stimulating effects, indica with sedating effects, and hybrids are perceived to be bred from the former two to fit the more personalized needs of consumers [ 23 , 24 , 35 , 37 ]. Interestingly, a recent study collected data characterizing various commercial products classified as sativa , indica , or hybrid and used supervised and unsupervised machine learning algorithms to subjective effect tags [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, many researchers hold that the differences in perceived effects between strain categories may be owing to other components of cannabis (ie, terpenes), which are rarely accurately reported to consumers [ 34 , 36 , 38 , 39 ]. Interestingly, some studies have found that products labeled as indica and sativa have similar concentrations of major cannabinoids but distinctly different concentrations of terpenes [ 23 , 40 , 41 ]. To date, hundreds of different cannabinoids and terpenes have been identified, all with varying pharmacological properties and outcomes [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations